Role of Fiber Length and Pore Former on the Porous Network of Carbon Paper Electrode and its Performance in PEMFC. Issue 4 (25th March 2014) - Maheshwari, P. H.; Gupta, C.; Mathur, R. B.
Abstract Porous conducting carbon paper has been recognized as one of the ideal materials to be used as an electrode backing in a fuel cell assembly. Carbon paper is prepared by the combined process of papermaking followed by composite formation. Two different studies, i.e. (i) using chopped carbon fiber of different lengths in the papermaking process, and (ii) introducing pore formers (blowing agents) in the sample during the resin impregnation/composite formation step, were adopted separately to control the porosity of the paper. The effect of the above processes on the various properties of the carbon paper electrode affecting its performance in a unit polymer electrolyte membrane fuel cell has been discussed. A maximum power density of 766 mW cm–2 has been achieved for carbon paper with 0.6 cm fiber length, an increase of nearly 12% as compared to 684 mW cm–2 for sample with 1.0 cm fiber length and tested under similar conditions. The introduction of pore former demonstrates increased performance of the fuel cell at high current densities.